Trading Costs and Exchange Delisting: The Case of Firms that Voluntarily Move from the American Stock Exchange to the Nasdaq - Clyde, Paul; Schultz, Paul; Zaman, Mir (Journal of Finance, 1997)
We examine 47 stocks that voluntarily left the American Stock Exchange from 1992 through 1995 and listed on the Nasdaq. We find that both effective and quoted spreads increase by about 100 percent after listing on the Nasdaq. These spread changes are consistent across stocks. In contrast, excess returns are positive when firms announce a switch from The American Stock Exchange to the Nasdaq. We are unable to explain this apparent contradiction.